2020
DOI: 10.1186/s13550-020-00721-2
|View full text |Cite
|
Sign up to set email alerts
|

Sapap3 deletion causes dynamic synaptic density abnormalities: a longitudinal [11C]UCB-J PET study in a model of obsessive–compulsive disorder-like behaviour

Abstract: Background Currently, the evidence on synaptic abnormalities in neuropsychiatric disorders—including obsessive–compulsive disorder (OCD)—is emerging. The newly established positron emission tomography (PET) ligand ((R)-1-((3-((11)C-methyl-(11)C)pyridin-4-yl)methyl)-4-(3,4,5-trifluorophenyl)pyrrolidin-2-one) ([11C]UCB-J) provides the opportunity to visualize synaptic density changes in vivo, by targeting the synaptic vesicle protein 2A (SV2A). Here, we aim to evaluate such alterations in the brain of the SAP90/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 81 publications
(115 reference statements)
0
14
0
Order By: Relevance
“…[ 11 C]UCB-J has now been used in monkeys ( Nabulsi et al, 2016 ), pigs ( Thomsen et al, 2020 ), mice ( Bertoglio et al, 2020 ), rats ( Thomsen et al, 2021b ), and humans ( Finnema et al, 2016 ) and show favourable brain penetration, fast uptake and acceptable washout kinetics. In rats and mice, various kinetic modelling was performed using an arterial blood sampling scheme or image-derived input function (IDIF) from the heart ( Bertoglio et al, 2020 ; Glorie et al, 2020 ; Thomsen et al, 2021b ). The 1TCM and 2TCM both work favourably with [ 11 C]UCB-J using the heart as an IDIF ( Bertoglio et al, 2020 ; Glorie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 C]UCB-J has now been used in monkeys ( Nabulsi et al, 2016 ), pigs ( Thomsen et al, 2020 ), mice ( Bertoglio et al, 2020 ), rats ( Thomsen et al, 2021b ), and humans ( Finnema et al, 2016 ) and show favourable brain penetration, fast uptake and acceptable washout kinetics. In rats and mice, various kinetic modelling was performed using an arterial blood sampling scheme or image-derived input function (IDIF) from the heart ( Bertoglio et al, 2020 ; Glorie et al, 2020 ; Thomsen et al, 2021b ). The 1TCM and 2TCM both work favourably with [ 11 C]UCB-J using the heart as an IDIF ( Bertoglio et al, 2020 ; Glorie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rats and mice, various kinetic modelling was performed using an arterial blood sampling scheme or image-derived input function (IDIF) from the heart ( Bertoglio et al, 2020 ; Glorie et al, 2020 ; Thomsen et al, 2021b ). The 1TCM and 2TCM both work favourably with [ 11 C]UCB-J using the heart as an IDIF ( Bertoglio et al, 2020 ; Glorie et al, 2020 ). The use of IDIF and whole-brain normalisation allows longitudinal studies in rodents since blood sampling often is laborious and error-prone.…”
Section: Discussionmentioning
confidence: 99%
“…Given the instrumental role of preclinical models in understanding neuropsychiatric and neurodegenerative disorders in parallel to the broad spectrum of diseases characterized by synaptic dysfunction, we previously described the application of [ 11 C]UCB-J in mice 15 and the utility of [ 11 C]UCB-J PET imaging in preclinical models to significantly advance our understanding of the pathophysiology and diagnosis of neurological disorders, including Huntington’s disease, 16 obsessive-compulsive disorder, 17 and spinal cord injury. 18 …”
Section: Introductionmentioning
confidence: 99%
“…In psychiatric research, [ 11 C]UCB-J has been used to measure synaptic density deficits in the Sapap3 knockout model of obsessive-compulsive disorder, through a longitudinal PET study in which an early decrease in radiotracer binding was reported in several brain regions of this model, including in the cortex, striatum, thalamus, and hippocampus (Glorie et al, 2020).…”
Section: Synaptic Vesicle 2a Positron Emission Tomography Tracers In ...mentioning
confidence: 99%